THE IMPLEMENTATION OF BARNEY VIDEO TO TEACH VOCABULARIES AT TK B PEJAJARAN SURABAYA (RETAIN, 2013)
ABSTRAK Vocabulary (kosakata) merupakan salah satu komponen penting dalam bahasa yang harus dikuasai sebelum menguasai ketrampilan berbahasa lainnya. Hal itu dikarenakan, tanpa menguasai kosakata, suatu gagasan tidak dapat tersampaikan dan semua ketrampilan tidak dapat dikuasai. Mengajar bahasa Inggris sebagai bahasa asing kepada anak- anak, terutama anak- anak TK merupakan hal yang tidak mudah karena mereka berada pada level awal dalam belajar sesuatu. Untuk menguasai bahasa Inggris dengan baik, seorang guru mengajar mereka dari komponen dasar yang disebut vocabulary (kosakata). Dalam mengenalkan atau mengajarkan kosakata- kosakata baru kepada anak- anak, guru menggunakan media. Media yang digunakan adalah video Barney. Dalam penelitian ini, peneliti merumuskan dua rumusan masalah, yaitu: 1) Bagaimana penerapan video Barney untuk mengajar kosakata di TK B pejajaran Surabaya? 2) Bagaimana respon siswa terhadap penerapan video Barney untuk mengajar kosakata di TK B Pejajaran Surabaya? Untuk mendapatkan data tentang penerapan dari video Barney untuk mengajar kosakata di TK B Pejajaran Surabaya, peneliti menggunakan descriptive- qualitative. Penelitian tersebut dilakukan dalam tiga pertemuan. Dia menggunakan observation checklist dan interview sebagai instrumen. Observation checklist nya digunakan dalam setiap pertemuan. Interview nya digunakan setelah pertemuan terakhir. Setelah mengumpulkan data, dia menyimpulkan bahwa menggunakan video Barney untuk mengajar kosakata sangat cocok untuk anak- anak TK. Hal itu dibuktikan bahwa mereka sangat antusias dalam mengikuti kegiatan belajar mengajar dan mereka menunjukkan respon yang baik terhadap penerapan video Barney dalam pembeajaran kosakata. Sebagai tambahan, berdasarkan wawancara, dia menyimpulkan bahwa video Barney memotivasi mereka dalam belajar kosakata karena mereka dapat mengingat kosakata dengan baik dan mengaplikasikannya. Dan terakhir, dengan menggunakan video Barney, anak- anak dapat termotivasi dalam belajar bahasa Inggris. Kata Kunci: video Barney, Taman kanak- kanak, kosakata ABSTRACT Vocabulary is one of important components of language that must be mastered before mastering language skills. It is because, without mastering vocabulary, one’s idea cannot be conveyed and all skills cannot be mastered. Teaching English as a foreign language to young learners, especially kindergarten students is not easy because they are at the early state to learn something. In order to master English well, teacher teaches them from the basic component called vocabulary. In recognizing or teaching new words to the students, teacher uses media. The media that is used is Barney video. In this study, the researcher formulates two research questions, there are: 1) How is the implementation of Barney video to teach vocabularies at TK B Pejajaran Surabaya? 2) How are the students’ responses toward the implementation of Barney video to teach vocabularies at TK B Pejajaran Surabaya? To obtain the data about the implementation of Barney video to teach vocabularies at TK B Pejajaran Surabaya, the researcher uses descriptive – qualitative research. It conducted in three meetings. She used Observation checklist, and interview as instruments. The observation checklist was done in every meeting. The interview was done after the last meeting. After collecting the data, she found that using Barney video to teach vocabularies was appropriate to kindergarten students. It proved that they were very enthusiastic in teaching and learning activity and they gave good responses toward the implementation of Barney video in learning vocabularies. In addition, based on interview, she found that Barney video motivated students in learning vocabularies because they can memorize vocabularies well and apply them. Finally, by using Barney video, the students get motivation in learning English. Key words: Barney video, kindergarten, vocabulary INTRODUCTION There are some reasons why English can be taught at kindergarten level. Kindergarten students are in the ages of acquirer language naturally (Clark, 2000; Dunn, 2011). Winarno, et al (2007:10) states that childhood is the best period to learn languages including English as a foreign language. Steinberg (1993) supports that the critical period for language- learning begins to close around five years old and ends after puberty. For those reasons, kindergarten students learn English easier than adults. Kindergarten is the early stage for students to learn something. Therefore the teaching English will be focused on introducing vocabulary items which are as the basis device to build up language for the starter language learners. Teaching vocabularies to kindergarten students can be frustrating for both teacher and students. As young learners, kindergarten students have special characteristics which are different from adults. They love playing, and learn best when they are enjoying themselves. Therefore teacher should include movement and involves the sense because their own understanding comes through hands and eyes and ears. They will understand if the teacher demonstrates it (Scott and Ytreberg, 1990: 2-5). For those reasons, teacher should be able to create a good atmosphere and applied suitable teaching techniques that can support the learning activities.. Kasbolah (1993:26) supports that the activities that can attract the children are singing, playing games, listening stories of their interest, and doing things. Teacher can find the fun activities such as singing, playing games, listening stories, and doing things in Barney video. Integrating Barney video into lesson can attract the students to learn vocabularies. Moreover, Barney video can stimulate the students to learn English with fun activities. Based on the statements above, the researcher formulates two research questions, those are, how is the implementation of Barney video to teach vocabularies and how is the students’ responses toward the implementation. Based on the statement problems above, the researcher can write the objectives of the study, those are, to describe the implementation of Barney video to teach vocabularies, and to find out the students’ responses toward the implementation. METHOD This study used a descriptive qualitative research. The subjects of this study were the teacher and the students B class of TK Pejajaran Surabaya. The study would conduct at B class. The total numbers of the students were 27 students. Researcher chose TK B Pejajaran Surabaya as the subject of the study because using Barney video to teach vocabularies had been implemented in that school. The researcher collected the data through some instruments. The instruments were observation checklist and semi- structured interview. The way to collect the data in this study was by observing the activity which is done during the implementation of Barney video to teach vocabularies at TK B Pejajaran Surabaya. After the activities were done, the researcher interviewed the students to gain the data about their responses after implementing Barney video to teach vocabularies. After getting the data, an analysis toward the data is needed. The data were analyzed by describing, interpreting and making the conclusion. The way of the teacher implementing Barney video was described based on the observation checklist. The students’ responses were obtained by interviewing the students. After analyzing the data, the researcher made a general conclusion about this study. RESULT AND DISCUSSION 1. Result of the Study In this part, the researcher describes the result of the observations which were done three times and interviewed with the students which were done after the implementation of Barney video to teach vocabularies. The first day of observation was held on Monday, April 15th, 2013 at 11.30 a.m. – 12.30 p.m. The second meeting was held on Thursday, April 18th, 2013 at 10 a.m. – 11.00 a. m. The third meeting or the last meeting of observation was held on Monday, April 22nd, 2013 at 11.30 a.m. – 12.30 p.m. In the Observation, the teacher used Barney video which entitled Moving and Grooving. The length of the video was about 40 minutes. The teacher divided it into two parts. The first 20 minutes of the video for the first meeting. The last 20 minutes of the video for the second meeting. In the last meeting, teacher used the whole 40 minutes of the video. Each meeting was 60 minutes. 1.1 Result of the First Observation In the first observation, the teacher used the first 20 minutes of the video. She played the video while explaining the some words to the students. Those words are clap and cross, clap on your stomach, clap on your shoulder, clap on your knee, clap on your hip, star, radio, clap your hand, stamp your feet, and shout hooray. 1.2 Result of the Second Observation In the second observation, the researcher used the last 20 minutes of the video. She played the video and explained some words to the students. Those words are, swimming, swimming pool, tortoise, and rabbit, run, and stop. 1.3 Result of the Third Observation In the last observation, the teacher played the whole video. After watching the video, the students are given tasks. The tasks were the students were given some pictures and they had to answer the questions by showing the pictures. And the other task was the students were divided into groups and each group had to answer the questions from the teacher. The teacher gave the questions based on Barney video, for instance: the teacher said “clap your hand”, so the group should have clapped their hands. 2. Discussion Teacher used video as a media to teach vocabularies to her students because it helped her to deliver the vocabularies to the students. Teaching both young learners and adults using video can motivate learners. For young learners, one of the aims of teaching English is to instill them the idea that language learning is a happy experience, and video creates an attractive enjoyable learning environment (Tomalin, 1991: 48). During observations, the teacher used Barney video which entitled Moving and Grooving. The contents of the video are interesting for children because the contents are about singing a song, dancing, playing game, and telling stories. According to Kasbolah (1993:26), the activities that can attract the children are singing, playing games, listening stories of their interest, and doing things. The variety of the activity in the video also supports the teaching and learning process. Since young learners have short attention and attention spans, the variety is a must in teaching young learners (Scott and Ytreberg, 1990: 5-7). The students’ responses toward the implementation of Barney video to teach vocabularies were known from the result of interview with the students. From the result, the researcher can conclude that the students gave good responses toward the implementation of Barney video to teach vocabularies. They are more excited joining the teaching and learning process when the teacher used Barney video in the class than the teacher did not use video. Tomalin (1991: 48) states that video creates an attractive enjoyable learning environment. That’s why the students like learning English through video. Moreover, the students were still excited joining the teaching and learning process using Barney video in the second and third observation. In the third observation, the teacher gave some exercises to the students to know the students’ understanding toward the vocabularies that had been learnt in the first and second meeting. CLOSING Conclusion The use of Barney video to teach vocabularies to young learners is one of the technique which appropriate and useful in teaching vocabularies for kindergarten students. The use of Barney video can help both teacher and students in EFL class. For the teacher, it helps her to teach vocabularies attractively. Since the students are young learners, the teacher should teach English as attractive as possible. For the students, they can learn English easily in a fun way. They can learn by watching, hearing, and demonstrating it since their own understanding comes through hands and eyes and ears. Besides, it can motivate the students in learning English. The students can see how the language is used, where the language is used, and when the language is used. Based on the data analysis on the previous chapter, the researcher concludes that the implementation of Barney video to teach vocabularies at TK B Pejajaran Surabaya is good and in line with the theory which have been explained in chapter II. From the first until the third observation, the teacher is able to use the Barney video in teaching vocabularies to kindergarten students well. From the data that had been got by the researcher by interviewing with the students, it shows that the students more interest learning English using Barney video. The students’ vocabularies in the third observation show that they do not get any difficulty learning English through Barney video. Therefore, it can be concluded that teaching vocabularies using Barney video can give contribution to the students in learning vocabularies. Suggestion Considering the result of this study, the researcher considers that it is necessary to serve several suggestions to English teacher dealing with the implementation of Barney video to teach vocabularies to young learners. In the teaching process, the teacher sometimes should use L2 to communicate with the students. The purpose is that the students will be familiar with the English words. For instance when the teacher greets the students, she should use L2 so that the students are familiar with the English words. Learning language is about habitual and recognizing the language itself. Furthermore the teacher has implemented Barney video to teach vocabularies to young learners well. REFERENCES Ary, D., Jacobs, L. C., & Sprensen, C. (2001, 2006). Introduction to Research in Education (Eight ed). USA: Wadsworth, Cengange Learning Brotherson, S. 2005. Understanding Brain Development in Young Children. Retrieved December 15, 2011 from http://infopeople.org/sites/all/files/past/2008/simply/Symplylrr_article1.doc Cameron, L. 2001. Teaching Languages to Young Learners. Cambridge: Cambridge University Press Clark, Baverly A. (2000). First and Second Language Acquisition in early Childhood. Retrieved Oct 18, 2011 from Eric Journal ED470889 Dunn, Opal. (2011). How young children learn English as Another Language. Retrieved November 26, 2011 from http://learenglishkids.britishcouncil.org/en/parents/articles/how-young-children-learn-english-another-language Finnochiaro, M. 1986. Techniques and Principles in Language Teaching. Oxford University Inc. Griffee, T. Dale. 1992. Songs in Action. New York: Practice Hall International, Ltd. Hornby, A. S. 1995. Oxford Advance Learner’s Dictionary. English: Oxford University Press Linse. 2005. Teaching English to Young Learners. Retrieved March 13, 2013 from http://ocw.metu.edu.tr/puginfile.php/2289/mod_resource/content/0/weekIV_teachingVovabulary.pdf Newman, A. 2010. Ask a Scientist. Retrieved December 15, 2011 from http://archive.nrc-cnrc.gc.ca/eng/dimensions/issue5/aaron_newman.html Patmonodewo, Soemiarti. 2000. Pendidikan Anak Pra Sekolah. Jakarta: PT. Rineka Cipta Pribilova, L. 2006. Teaching Vocabulary to Young Learners. Bachelor Work, Masaryk University. Rammal, S. M. 2005. Using Video in the EFL classroom. Ein-Shams University, Cairo, Egypt. Retrieved April 16, 2013 from http://www3.telus.net/linguisticsissues/using%20video Scott, W. A. and Ytreberg, L. H. 1990. Teaching English to Children. New York: Longman Shin, J. K. nd. Teaching English to Young Learners. Retrieved February 28, 2013 from http://www.nstru.ac.th/portal/data_resource/NEWS/2009/INSIDE/FILE/1232942687_087864500.pdf Steinberg, D.D. 1993. An Introduction To Psycholinguistics. New York: Longman Williams, R. T. and Lutes, P. nd. Using Video in the ESL Classroom. Retrieved March 27, 2013 from http://www.takamatsu-u.ac.jp/library/06_gakunaisyupan/kyo/no48/001-013_williams.pdf Winarno, et al (2007:10) states that childhood is the best period to learn languages including English as a foreign language. Yassaei, S. 2012. Using original Video and Sound Effects to Teach English. Retrieved February 28, 2013 from http://americanenglish.state.gov/files/ae/resource_files/50_1_4_yassaei.pdf